2018
DOI: 10.1016/j.combustflame.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating thermoacoustic properties of heating appliances considering the burner and heat exchanger as acoustically active elements

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…By comparing the results of these two approaches, they confirmed that the burner and the HEX can be treated as individual network elements as long as the flow field reaches a uniform velocity profile in the region between the flame tip and the HEX. This is in line with the findings by Hosseini et al 94,97 The calculations of the scattering matrix in Strobio Chen et al 92 also revealed that the HEX enhances a pre-existing ITA mode (see section 10.4.1).…”
Section: Modelling Of the Interaction Between Burner And Hexsupporting
confidence: 87%
See 4 more Smart Citations
“…By comparing the results of these two approaches, they confirmed that the burner and the HEX can be treated as individual network elements as long as the flow field reaches a uniform velocity profile in the region between the flame tip and the HEX. This is in line with the findings by Hosseini et al 94,97 The calculations of the scattering matrix in Strobio Chen et al 92 also revealed that the HEX enhances a pre-existing ITA mode (see section 10.4.1).…”
Section: Modelling Of the Interaction Between Burner And Hexsupporting
confidence: 87%
“…Hydrodynamic interaction. Numerical simulations were conducted by Hosseini et al [94][95][96] to elucidate whether the burner and the HEX can be decoupled and modelled by independent transfer functions. Their numerical domain is shown in Figure 51.…”
Section: Modelling Of the Interaction Between Burner And Hexmentioning
confidence: 99%
See 3 more Smart Citations